The genomic response to song and the representation of complex sounds in the auditory system of zebra finches - Velho, Tarciso André Ferreira (2008)
The consolidation of long-lasting sensory memories requires the activation of gene expression programs. However, to fully understand the contribution of genomic events necessary for sensory learning, it is necessary to characterize the components involved in this response, their induction kinetics, and the possible functional interactions among individual components. Birdsong represents one of the best natural behaviors to study gene expression induced by auditory stimulation in awake, freely behaving animals. The present work addresses the properties and functional consequences of the genomic response to birdsong in zebra finches (Taeniopygia guttata), with a specific focus on the caudomedial nidopallium (NCM), a cortical-like auditory area involved in song auditory processing and memorization. We found that song induces a wellorchestrated cascade of gene expression that includes early and late genes. Early genes are co-expressed by NCM neurons and their induction is regulated by the mitogen-activated protein (MAP) kinase pathway. In addition, we also found that the induction of early genes is locally modulated by norepinephrine. We have also identified two late genes, syn2 and syn3, whose induction is repressed by early song-induced proteins genes in NCM. Functionally, we show that blockade of this response by α-adrenergic antagonists disrupts the long-term maintenance of long-lasting neuronal changes triggered by song. Finally, we show that the pattern of early song-induce gene expression in NCM is stimulus dependent. These patterns also indicate the existence of functional subdomains of more or less selectivity towards conspecific songs. Overall, these results help us understand the functional significance of the genomic response to song and the functional organization of sound representation in a higher order auditory area of the songbird brain.